SEEKING EFFECTIVE TIME OF PLANTING FOR IBA TREATED JOJOBA (S IMMONDSIA CHINENSIS) CUTTINGS UNDER POLY-TUNNEL - M. A. Bashir; G. Hussain; M. Ahmad; M. A. Anjum (Journal of Animal and Plant Sciences, 2013)
Semi-hardwood cuttings of jojoba (Simmondsia chinensis) treated with 4000 mg L-1 IBA, were planted at fortnightly interval starting from 1st October to the end of March of next year under microclimatic conditions of polythene sheet tunnel during two consecutive years. Average of two years data depicted that planting time of cuttings significantly affected mortality (%), rooted cuttings (%) out of total cuttings and rooted cuttings (%) out of healthy green cuttings. The cuttings planted on 1st November resulted in maximum rooted cuttings (56%) out of total cuttings with mortality (33%) and rooted cuttings (82%) out of healthy green cuttings, followed by the cuttings planted on 16th October which showed 53% rooted cuttings out of total cuttings with 36% mortality and 83% rooted cuttings out of healthy green cuttings. Both the time of planting remained statistically at par. Minimum rooted cuttings (2%) with minimum rooted cuttings out of healthy green cuttings (3%) were found in the cuttings planted on 16th March. Inside the poly-tunnel the optimumtemperature for rooting of cuttings were about 14oC (minimum) and 36oC (maximum) with relative humidity (52-80%). The minimum temperature less than 10oC inside the poly-tunnel is not favorable for rooting of cuttings even under the favorable R.H. range.
Keywords: Simmondsia chinensis; poly-tunnel; cuttings; propagation; rooting; IBA